CALCULATION OF PROBABILITY OF TRISO PARTICLE FAILURE USING TIMCOAT AND PEBBED CODE - Rokhmadi Wijaya; Bebeh Wahid Nuryadin; Khotib Maulani; Topan Setiadipura (SIGMA EPSILON - Buletin Ilmiah Teknologi Keselamatan Reaktor Nuklir, 2020)
CALCULATION OF PROBABILITY OF TRISO PARTICLE FAILURE USING TIMCOAT AND PEBBED CODE. The calculation of the failure probability for fuel particles (TRISO) in the HTGR type reactor has been successfully carried out. This study aimed to estimate the failure probability of the fuel particles in the HTR-10 and HTR-PM, as well as to analyze the fuels of those reactors by varying the SiC thickness. The initial layer thickness of SiC in the HTR-10 and HTR-PM is 35 µm. The PEBBED code was used to simulate calculations resulting in the power distribution data, which is then compared with the results from the TIMCOAT simulation process. The TIMCOAT simulation calculation results, which are based on the SiC thickness variation, showed that the thickness failure is smaller if applied to the HTR-10 and HTR-PM. Based on the comparison between the two reactors, the failure probability of HTR-PM fuel particle has the value smaller than that of the HTR-10 with the difference of 10-5 .Keywords: failure particle, HTR-10, HTR-PM, TRISO, TIMCOAT.